Complicated uveal cataracts after intrauterine viral infection: a case report (Ukrainian Journal of Ophthalmology, 2025)
We report a case of complicated binocular cataract caused by intrauterine uveitis of mixed viral etiology (herpes simplex virus 1/2, cytomegalovirus and Epstein-Barr virus), and describe the management algorithm, surgical treatment features and treatment outcome.
Keywords: complicated cataract; intrauterine TORCH infections